2020
DOI: 10.1002/er.6015
|View full text |Cite
|
Sign up to set email alerts
|

Improvement and validation of a sub‐channel analysis code for a lead‐cooled reactor with wire spacers

Abstract: Summary The fuel rods in the lead‐based fast reactor (LFR) are usually supported by wire spacer, and the presence of the wire results in the complexity of the thermal‐hydraulic analysis in rod bundles. In this study, several previous experimental research about lead‐bismuth eutectic flowing through the rod bundle are investigated. Based on the collected experimental data, a series of flow and heat transfer correlations in the wire‐fixed rod bundle are compared and evaluated. The recommended correlations are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…4) SACOS-PB (Wang et al, 2013a), which is concluded that the hexagonal fuel assembly is the best choice for the LBE fast reactor by analyzing the temperature distribution of the fuel assembly and diverse component types. Wu et al (2021) improved SACOS-PB, and Wang et al (2021) utilized it for flow blockage incident analysis. 5) ANTEO+ (Lodi et al, 2016a), which can be used to calculate liquid metal cooled fast reactors, including sodium, lead, LBE, and is suitable for a variety of geometric structures such as bare-rod, grid-type spacers, and wire-type spacers.…”
Section: Introductionmentioning
confidence: 99%
“…4) SACOS-PB (Wang et al, 2013a), which is concluded that the hexagonal fuel assembly is the best choice for the LBE fast reactor by analyzing the temperature distribution of the fuel assembly and diverse component types. Wu et al (2021) improved SACOS-PB, and Wang et al (2021) utilized it for flow blockage incident analysis. 5) ANTEO+ (Lodi et al, 2016a), which can be used to calculate liquid metal cooled fast reactors, including sodium, lead, LBE, and is suitable for a variety of geometric structures such as bare-rod, grid-type spacers, and wire-type spacers.…”
Section: Introductionmentioning
confidence: 99%